IMPACTS OF ELECTRONIC BILLING ON BUSINESSES IN CIUDAD DEL ESTE - Machesk de Mujica, Andrea; Tamara González Durant, Daniela; Elizabeth Bareiro Cantero, Fátima; Ortellado González, Zulma (Revista Gênero e Interdisciplinaridade, 2023)
The objective of this work is to analyze how the implementation of electronic invoices in Ciudad del Este affects companies and their consumers. The research developed on the following pages consists of three units: Unit I: Companies, Unit II: Invoices, Unit III: Electronic Billing. This research was carried out with a qualitative research approach, the level of research is exploratory, the survey was used as a data collection technique, which consisted of a questionnaire of open questions, addressed to our sample, which corresponds to 100% of the population. consisting of 15 merchants from Ciudad del Este. The results obtained showed that the majority of merchants consider that it positively impacts businesses and their consumers since electronic invoicing is safer than the traditional system. They also highlighted that with the implementation of electronic invoices, economic costs can be considerably reduced. for companies, and will help reduce tax evasion.